Activity of convalescent and vaccine serum against SARS-CoV-2 Omicron - Carreño, Juan Manuel; Alshammary, Hala; Tcheou, Johnstone; Singh, Gagandeep; Raskin, Ariel J.; Kawabata, Hisaaki; Sominsky, Levy A.; Clark, Jordan J.; Adelsberg, Daniel C.; Bielak, Dominika A.; Gonzalez-Reiche, Ana Silvia; Dambrauskas, Nicholas; et al. (Nature (London), 2022)
The Omicron (B.1.1.529) variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was initially identified in November 2021 in South Africa and Botswana, as well as in a sample from a traveller from South Africa in Hong Kong 1 , 2 . Since then, Omicron has been detected globally. This variant appears to be at least as infectious as Delta (B.1.617.2), has already caused superspreader events 3 , and has outcompeted Delta within weeks in several countries and metropolitan areas. Omicron hosts an unprecedented number of mutations in its spike gene and early reports have provided evidence for extensive immune escape and reduced vaccine effectiveness 2 , 4 – 6 . Here we investigated the virus-neutralizing and spike protein-binding activity of sera from convalescent, double mRNA-vaccinated, mRNA-boosted, convalescent double-vaccinated and convalescent boosted individuals against wild-type, Beta (B.1.351) and Omicron SARS-CoV-2 isolates and spike proteins. Neutralizing activity of sera from convalescent and double-vaccinated participants was undetectable or very low against Omicron compared with the wild-type virus, whereas neutralizing activity of sera from individuals who had been exposed to spike three or four times through infection and vaccination was maintained, although at significantly reduced levels. Binding to the receptor-binding and N-terminal domains of the Omicron spike protein was reduced compared with binding to the wild type in convalescent unvaccinated individuals, but was mostly retained in vaccinated individuals. Sera from unvaccinated, vaccinated, and previously infected and vaccinated individuals show reduced neutralizing and spike protein-binding activity towards the Omicron (B.1.1.529) variant of SARS-CoV-2 compared to other variants.